1997
DOI: 10.1073/pnas.94.10.5372
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-linked mitigation of allergic responses to wheat

Abstract: Thioredoxin, a ubiquitous 12-kDa regulatory disulfide protein, was found to reduce disulfide bonds of allergens (convert SOS to 2 SH) and thereby mitigate the allergenicity of commercial wheat preparations. Allergenic strength was determined by skin tests with a canine model for food allergy. Statistically significant mitigation was observed with 15 of 16 wheat-sensitive animals. The allergenicity of the protein fractions extracted from wheat f lour with the indicated solvent was also assessed: the gliadins (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 36 publications
(35 reference statements)
4
87
0
1
Order By: Relevance
“…The potent food allergens are known to be very stable in in vitro pepsin digestion, whereas most dietary proteins are readily digestible (27). The pepsin digestibility assay is thus considered one of the major ways to identify food allergens (28)(29)(30). To determine the relative stability of AmA1 to the extremes of pH and pepsin protease encountered in the mammalian digestive tract, the protein extracts of transgenic tubers were subjected to pepsin digestibility.…”
Section: Simulated Gastric Fluid-and Simulated Intestinal Fluid-inducedmentioning
confidence: 99%
“…The potent food allergens are known to be very stable in in vitro pepsin digestion, whereas most dietary proteins are readily digestible (27). The pepsin digestibility assay is thus considered one of the major ways to identify food allergens (28)(29)(30). To determine the relative stability of AmA1 to the extremes of pH and pepsin protease encountered in the mammalian digestive tract, the protein extracts of transgenic tubers were subjected to pepsin digestibility.…”
Section: Simulated Gastric Fluid-and Simulated Intestinal Fluid-inducedmentioning
confidence: 99%
“…3) The disulfide bonds in the bean proteins were examined by the fluorescent labeling method. 4) Bean flour (200 mg) was mixed with 2 ml of extraction buffer (30 mM Tris-HCl, pH 7.9, containing 1 mM PMSF and 0.02% NaN 3 ), and centrifuged at 10;000 Â g for 15 min. Forty ml of supernatant (100 mg protein) was incubated for 20 min at room temperature with the following reduction reagents or enzymes in a final volume of 100 ml: (i) 0.5 mM DTT, (ii) 10 mM mercaptoethanol, (iii) 0.5 mM DTT and 1.6 mg thioredoxin, (iv) 2.5 mM NADPH, 1.6 mg thioredoxin, and 1.4 mg thioredoxin reductase, and (v) 2.5 mM NADPH, 2 mM glutathion, and 1 mg glutathione reductase.…”
mentioning
confidence: 99%
“…Buchanan and colleagues (Buchanan et al 1997;del Val et al 1999) reported that when structure of the major allergens from these foods is disrupted by reduction of disulfide bonds, the allergens were strikingly sensitive to pepsin digestion and lost their ability to elicit allergic reactions in previously sensitized dogs. Standardization of the assay conditions (such as pepsin concentration, pH, and temperature) has been described in the U.S. Pharmacopia (1990) and is sometimes referred to as SGF.…”
Section: Methodsmentioning
confidence: 99%